Figurative Language in Lany’s Malibu Nights Album: Types and Emotional Meanings - Nala Annisa Danin; Ghina Aninnasi; Theofani Donita Padang; Rahmadsyah Rangkuti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The use of figurative language in music is a crucial element that allows songwriters to communicate complex human emotions that literal language often fails to capture. While many studies have explored stylistic devices in popular music, a gap persists between general stylistic analysis and the specific ways contemporary artists use these tools to construct narratives of profound emotional distress. This study aims to identify the types of figurative language used in LANY’s album Malibu Nights and to explain how these devices function as expressions of the speaker's emotional journey. Using a descriptive qualitative method and Perrine’s (1992) theory, the research analyzed the lyrics of nine tracks from the album. The findings reveal nine types of figurative language: metaphor, simile, personification, synecdoche, paradox, symbol, hyperbole, apostrophe, and understatement. The data analysis shows that metaphor is the most dominant device, accounting for 39,39% of the total findings, followed by hyperbole at 19,70%, while other devices, such as personification and simile, appear at lower frequencies. Ultimately, this study concludes that figurative language is not merely an aesthetic addition but a primary linguistic vehicle that bridges the gap between private suffering and universal resonance, successfully articulating the multifaceted nature of human resilience within modern songwriting.